Long-term effects of altered pH and temperature on the feeding energetics of the Antarctic sea urchin, Sterechinus neumayeri - Morley, Simon A., Suckling ,Coleen C., Clark ,Melody S., Cross ,Emma L.; and Peck, Lloyd S. (Biodiversity, 2016)
This study investigated the effects of long-term incubation to near-future combined warming (+2 °C) and ocean acidification (−0.3 and −0.5 pH units) stressors, relative to current conditions (−0.3 °C and pH 8.0), on the energetics of food processing in the Antarctic sea urchin, Sterechinus neumayeri. After an extended incubation of 40 months, energy absorbed, energy lost through respiration and lost as waste were monitored through two feeding cycles. Growth parameters (mass of somatic and gonad tissues and the CHN content of gonad) were also measured. There were no significant effects of combined ocean acidification (OA) and temperature stressors on the growth of somatic or reproductive tissue. Despite more food being consumed in the low temperature control, once food processing and maintenance costs were subtracted, there were no significant effects of treatment on the scope for growth. The biggest significant differences were between amounts of food consumed during the two feeding cycles. More food was consumed by the low temperature (0 °C) control animals, indicating a potential effect of the changed conditions on digestive efficiency. Also, in November, more food was consumed, with a higher absorption efficiency, which resulted in a higher scope for growth in November than September and may reflect increased energetic needs associated with a switch to summer physiology. The effect of endogenous seasonal cycles and environmental variability on organism capacity is discussed.
Keywords: Carbonate saturation; climate change; dept.egm; echinoderm; energetics; ocean acidification; peer-reviewed; physiology; resilience

No ocean acidification effects on shell growth and repair in the New Zealand brachiopod Calloria inconspicua (Sowerby, 1846) - Cross, Emma L.; Peck, Lloyd S.; Lamare, Miles D.; Harper, Elizabeth M. (ICES Journal of Marine Science, 2016)
Surface seawaters are becoming more acidic due to the absorption of rising anthropogenic CO2. Marine calcifiers are considered to be the most vulnerable organisms to ocean acidification due to the reduction in the availability of carbonate ions for shell or skeletal production. Rhychonelliform brachiopods are potentially one of the most calcium carbonate-dependent groups of marine organisms because of their large skeletal content. Little is known, however, about the effects of lowered pH on these taxa. A CO2 perturbation experiment was performed on the New Zealand terebratulide brachiopod Calloria inconspicua to investigate the effects of pH conditions predicted for 2050 and 2100 on the growth rate and ability to repair shell. Three treatments were used: an ambient pH control (pH 8.16), a mid-century scenario (pH 7.79), and an end-century scenario (pH 7.62). The ability to repair shell was not affected by acidified conditions with >80% of all damaged individuals at the start of the experiment completing shell repair after 12 weeks. Growth rates in undamaged individuals >3 mm in length were also not affected by lowered pH conditions, whereas undamaged individuals <3 mm grew faster at pH 7.62 than the control. The capability of C. inconspicua to continue shell production and repair under acidified conditions suggests that this species has a robust control over the calcification process, where suitable conditions at the site of calcification can be generated across a range of pH conditions.
Keywords: dept.egm; peer-reviewed

Blue Economy - Germond-Duret, Celine; Garland, Michaela; Heidkamp, C. Patrick; Morrissey, John (International Encyclopedia of Geography, 2016)
Geography has engaged in insightful discussions on how to understand, analyze, criticize, and implement the blue economy. United Nations agencies, Small Island Developing States, and increased academic interest in oceans have played important roles in the global adoption of the blue economy idea, that is, the sustainable exploitation of marine and coastal resources. Geographical research on the blue economy has addressed key themes such as economic and political discourse, relational thinking and assemblage, sustainability and just transitions, and blue economy risks.
Keywords: coastal and marine geography; dept.egm; economic development; environmental management; sustainable development

The Kyrgyz Republic,1 central Asia, and daily life engagement - Yacher, L. (Arab World Geographer, 2016)
Keywords: Central Asia; Kyrgyzstan; dept.egm; geographical thought; life satisfaction; perception; ⛔ No DOI found

The role of magnetic agents in shaping post-disaster land use - Zavar, Elyse (Land Use Policy, 2016)
Three neighborhoods in Lexington, Kentucky, share a common flood history, including property acquisitions, as a means to mitigate against flooding; yet, the interactions of residents with the buyout landscapes vary significantly among the neighborhoods. Although the same institutions and structural controls implemented flood buyout programs in all three neighborhoods, semi-structured interviews illustrate that differing perspectives, personalities, and neighborhood politics shaped unique identities and land uses for the acquired properties in each neighborhood. Varying levels of resident engagement with the buyout landscape resulted in a range of attitudes towards hazard preparation, management, and mitigation, thus leaving some neighborhoods more resilient to future flooding than others. This study explores key residents, termed magnetic agents, who drove neighborhood civic action and land uses on the open space created through floodplain property acquisition. This research indicates magnetic agents can serve as important partners for local governments and non-governmental organizations (NGOs) in building community-based projects aimed at reducing vulnerability to flood events and instituting high utility land uses on floodplain buyout open space.(C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Agency; Floodplain buyout; Kentucky; Land management; Lexington; Resiliency; United States; dept.egm; flooding; floodplain; hazard management; land management; land use planning; neighborhood; open space

Especies de jaltomata schltdl. (solanaceae) con néctar rojo, tres nuevas combinaciones nomenclaturales y un nuevo taxón del noreste de perú - Gonzalez, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2016)
Keywords: dept.egm; ⚠️ Invalid DOI

The Modifiable Conceptual Unit Problem demonstrated using pollen and seed dispersal - Miller, Matthew D (Global Ecology and Conservation, 2016)
The Modifiable Areal Unit Problem (MAUP) is a famous issue in spatial analysis that states the output of a spatial analysis is influenced by the spatial extent of the units used in the analysis. This study demonstrates that the MAUP is accompanied with another intractable spatial issue in spatial modeling; the Modifiable Conceptual Unit Problem (MCUP). The MCUP states that the conceptualization of spatial processes impacts the output of spatial analysis and occurs when a model with one spatial dimension is applied to a spatial model with more than one spatial dimension. This study demonstrates the MCUP by developing three conceptual models of dispersal and showing how they produce different results even when given the same initial dispersal curves and areal units. Three conceptual models of dispersal (sum of curve points model, area of distance range model, and the volume of distance range model) are described and applied to a grid landscape with a single point of dispersal and a grid landscape with multiple points of dispersal. A Geographic Information System (GIS) is used to evaluate how the models differ in their distribution of pollen or seeds across the landscapes. The three models of dispersal are each valid conceptualizations of the dispersal process, but when given the same dispersal curve parameters, they produce different distributions of dispersed items across grid landscapes. The sum of curve points model is the least complicated model because it only uses a few points from the defined dispersal curve. The area of distance range model uses the entire dispersal curve, but is based on a single dimension of space and thus conceptually abstracted from the grid landscape. The volume of distance range model uses the two spatial dimensions present in the grid landscape and thus is the most conceptually sound model of the three. The underlying conceptualization of the dispersal process can impact the results of dispersal models. Applying dispersal curves with one spatial dimension to grids with two spatial dimensions makes inherent assumptions about the conceptualization of dispersal. This study highlights the necessity of researchers to declare their conceptual models of dispersal when applying modeled dispersal curves to grid landscapes. © 2016 The Author.
Keywords: Conceptual; Dispersal; Grid; MAUP; Pollen; Spatial; dept.egm

Land use change on US floodplain buyout sites, 1990-2000 - Zavar, Elyse; Hagelman, III, Ronald R. (Disaster Prevention and Management, 2016)
Purpose - The Federal Emergency Management Agency provides guidelines for the management of open space created through property acquisition (buyouts); however, land use decisions are primarily left to local governments manifesting in a variety of uses. The purpose of this paper is to provide a land use assessment of buyout sites, to describe the changes in those uses that have occurred during a ten-year period from 1990 to 2000, and to offer an assessment of management approaches employed across these sites. Design/methodology/approach - Using a mixed-methods approach consisting of a land use classification survey and a semi-structured questionnaire of floodplain managers, this study explores the land use trends at buyout sites, diverse approaches local governments take in managing the open spaces created through floodplain buyout programs, and the successes and challenges communities face in open space management. Findings - Results indicate strong support from floodplain managers for property acquisition and several cases emerged where communities put their newly acquired public land to creative uses. However, the opportunity to leverage these properties for greater public values is largely being missed, primarily because of limited funding. Practical implications - The analysis indicates strong support among floodplain managers for the buyout approach; however, additional resource-sharing and funding opportunities are needed to increase the utility of buyout properties. Originality/value - By evaluating the long-term management strategies floodplain managers utilize on buyout sites, this study adds to an underrepresented area of scholarship and is of value to practitioners, government officials, and academics.
Keywords: Buyout; Disaster mitigation; Floodplain management; Land use; dept.egm